Nanosized titania modified with tungsten and silver: Microstructural characterisation of a multifunctional material - Tobaldi, D. M.
With the ever-growing interest in nanotechnologies, the area of metal oxides is playing an increasingly dominant role. Amongst them, titanium dioxide (TiO2) nanoparticles are attracting increasing interest, owing to their unique physicochemical properties, and widespread applications - i.e. photocatalysis, energy materials, antibacterial agents, gas-sensors. We characterised the microstructure of titania nanopowders - synthesised via an aqueous sol-gel method and modified with silver and/or tungsten - using XRD data, through the whole powder pattern modelling (WPPM) procedure. An overall linear dependence of the lattice volume expansion was observed - the volume increased with the lowering of the crystalline domain size. Concerning the dislocation density, no specific trend depending on the modifying cation was reported. However, for the samples fired at 600 degrees C, the undoped titania sample had a much larger number of screw dislocations in the rutile phase, while the Ag-modified sample had a much greater number of edge dislocations in the anatase phase. (C) 2013 Elsevier B.V. All rights reserved.